Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1.5x\left(x^2+2x-1\right)-3x^2\left(x-2\right)=5x^3+10x^2-5x-3x^3+6x^2\)
\(=2x^3+16x^2-5x\)
\(=\left(2x^3-x\right)+\left(16x^2-4x\right)\)
\(=x\left(2x^2-1\right)+4x\left(4x-1\right)\left(ĐCCM\right)\)
a) \(2x^2y^2-\frac{4}{3}x^2y+2xy\)
\(=xy\left(2xy-\frac{4}{3}x+2\right)\)
b) 2xy2.(x + 5y) - 4xy(5y + x)
= (5y + x)(2xy2 - 4xy)
= 2xy(5y + x)(y - 2)
c) 25 - 4x2 - y2 + 4xy
= 25 - (4x2 - 4xy + y2)
= 52 - (2x + y)2
= (5 - 2x - y)(5 + 2x + y)
d) x2 + 4x - 2xy - 4y +y2
= (x2 - 2xy + y2) + (4x - 4y)
= (x - y)2 + 4(x - y)
= (x - y)(x - y + 4)
e) 12y3 - 3x2y + 12xy - 12y
= 3y(4y2 - x2 + 4x - 4)
= 3y[4y2 - (x - 2)2]
= 3y(2y - x + 2)(2y + x - 2)
f) 64x4 + y4
= (8x2)2 + 16x2y2 + y4 - 16x2y2
= (8x2 + y2)2 - (4xy)2
= (8x2 + y2 - 4xy)(8x2 + y2 + 4xy)
a) \(2x^2y^2-\frac{4}{3}x^2y+2xy\)
b) \(2xy^2\left(x+5y\right)-4xy\left(5y+x\right)\)
\(=\left(x+5y\right)\left(2xy^2-4xy\right)\)
\(=2\left(x+5y\right)\left(xy^2-2xy\right)\)
c) \(25-4x^2-y^2+4xy\)
\(=25-\left(4x^2+y^2-4xy\right)\)
\(=5^2-\left[\left(2x\right)^2-2.2x.y+y^2\right]\)
\(=5^2-\left(2x-y\right)^2\)
\(=\left(5-2x+y\right)\left(5+2x-y\right)\)
d) \(x^2+4x-2xy-4y+y^2\)
\(=\left(x^2-2xy+y^2\right)+\left(4x-4y\right)\)
\(=\left(x-y\right)^2+4\left(x-y\right)\)
\(=\left(x-y\right)\left(x-y\right)+4\left(x-y\right)\)
\(=\left(x-y\right)\left(x-y+4\right)\)
e) \(12y^3-3x^2y+12xy-12y\)
f) \(64x^4+y^4\)
\(=\left(8x^2\right)^2+16x^2y^2+\left(y^2\right)^2-16x^2y^2\)
\(=\left(8x^2+y^2\right)^2-\left(4xy\right)^2\)
\(=\left(8x^2+y^2+4xy\right)\left(8x^2+y^2-4xy\right)\)
Bài làm
a) 2x2y - 4xy2 + 6xy
= 2xy( x - 2y + 3 )
b) 4x3y2 - 8x2y3 + 2x4y
= 2x2y( 2xy - 4y2 + x2 )
c) 9x2y3 - 3x4y2 - 6x3y2 + 18y4
= 3y2( 3x2y - x4 - 2x3 + 6y2 )
d) 7x2y2 - 21xy2z + 7xyz - 14xy
= 7xy( xy - 3yz + z - 2 )
# Học tốt #
\(1,x^3-x=x\left(x^2-1\right)=x\left(x^2-1^2\right)=x\left(x-1\right)\left(x+1\right)\)
\(2,4ax^3-ax=ax\left(4x^2-1\right)=ax\left[\left(2x\right)^2-1^2\right]\) \(=ax\left(2x-1\right)\left(2x+1\right)\)
\(3,x^3-2x^2+x\)
\(=x^3-x^2-x^2+x\)
\(=\left(x^3-x^2\right)-\left(x^2-x\right)\)
\(=x^2\left(x-1\right)-x\left(x-1\right)\)
\(=\left(x-1\right)\left(x^2-x\right)=\left(x-1\right).x\left(x-1\right)=x\left(x-1\right)^2\)
\(4,y-4xy+4x^2y\)
\(=y\left(1-4x+4x^2\right)\)
\(=y\left(1^2-2.1.2x+\left(2x\right)^2\right)^{ }\)
\(=y\left(1-2x\right)^2\)
a,\(2x^2-8x+y^2+2y+9=0\)
\(\Rightarrow2\left(x^2-4x+4\right)+\left(y^2+2y+1\right)=0\)
\(\Rightarrow2\left(x-2\right)^2+\left(y+1\right)^2=0\)
Mà \(2\left(x-2\right)^2\ge0\forall x\); \(\left(y+1\right)^2\ge0\forall y\)
\(\Rightarrow2\left(x-2\right)^2+\left(y+1\right)^2\ge0\forall x;y\)
Dấu "=" xảy ra<=> \(\hept{\begin{cases}2\left(x-2\right)^2=0\\\left(y+1\right)^2=0\end{cases}\Rightarrow\hept{\begin{cases}x=2\\y=-1\end{cases}}}\)
Vậy x=2;y=-1
a) 4x3y2 - 8x2y3 + 2x4y
= 2x2y ( 2xy - 4y2 + x2)
= 2x2y (x2 + 2xy + y2 - 5y2)
= 2x2y ( x + y - \(\sqrt{5}\).y)( x + y + \(\sqrt{5}\).y)
b) 2x2y - 4xy2 + 6xy
= 2xy ( x - 2y + 3)
c) - 3x-6xy + 9xz
= -3x( 1 + 2y - 3z)
\(\left(2x-y\right)^3-3x.\left(y-2x\right)^2-4x^2+4xy-y^2\)
\(=\left[\left(2x-y\right)^3-3x.\left(y-2x\right)^2\right]-\left[4x^2+4xy-y^2\right]\)
\(=\left[\left(2x-y\right)^2.\left(2x-y\right)-3x.\left(y-2x\right)^2\right]-\left(2x-y\right)^2\)
\(=\left[\left(y-2x\right)^2.\left(2x-y-3x\right)\right]-\left(2x-y\right)^2\)
=\(\left(y-2x\right)^2.\left(-x-y\right)-\left(2x-y\right)^2\)
\(=\left(y-2x\right)^2.\left(-x-y-1\right)\)
Chúc bạn học tốt